triple jump comparative study results - Zerf, Mohammed; Moulay, Idris Mokkedes; Bengoua, Ali; Bendahmane, Mohammed Nasreddine; Guebli, Abdelkader (My University, 2015)
The purposes of this study were to describe and compare the techniques used by elite word triple jumper and the Algerian elite time to determine the impact of correct models phases whom allowing the elite to beat world record. The subjects were three world elite and three currently national elite. In the lack of new technology, the base of our study thinks about 1- Decrypt the practice model and distribution of the phase between our champions (world-national). 2- Compart the relationship of the practice model or style between our champions (world-national). 3- Compare the difference in practice model between our champions (world-national). For that, we have shoes the Analysis of variance and correlation of the distances achieved in tudent to compare implementation distribution of phases (hop, step and jump) with the results accuses. Our aim for this research is to: Using the biomechanics to determine errors and integrated the modern scientific methods into the program monitoring sports. phrases to improve their performances during training and competitions.
Keywords: phase / techniques OF triple jump